A new approach for the determination of technological parameters for hydroabrasive cutting of materials: Ein neuer Ansatz zur Ermittlung der technologischen Parameter für Wasserstrahlschneiden. Issue 5 (18th May 2016) - Valíček, J.; Harničárová, M.; Hlavatý, I.; Grznárik, R.; Kušnerová, M.; Hutyrová, Z.; Panda, A.
Abstract : A method for the design of a technology for the abrasive waterjet cutting of materials is based on the determination of the constant of cuttability of materials using an abrasive waterjet Kawj according to four different versions. Version A, where three deformation parameters are measured on the test cut/sample, namely selected depth hx [mm], local roughness Rax [μm] at depth hx and local deviation of the cut trace from the normal plane Yretx at depth hx . Version B, where merely two deformation parameters are measured, namely the reference depth het [mm] and deviation of the cut trace from the normal plane Yretx [mm] or, according to version C, where one parameter is mearured, namely either the ultrasonic wave speed vLUZ [m · s –1 ] or Young's modulus Emat [MPa]; Kawj being calculated from relevant deformation parameters. The last option is version D, where the design of the whole technology is carried out by calculation of Kawj according to the Young's modulus Emat or according to the ultrasonic wave speed vLUZ of the cut material.